Efficiency study of nickel-containing glass-fiber catalysts for CO2 methanation - Ia.A. Mikhailov; M.V. Grigoriev; K.A. Motaev; A.V. Matigorov; S.A. Lopatin; A.N. Zagoruiko; A.V. Elyshev (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
The work is dedicated to the synthesis and investigation of Ni-containing catalysts based on glass-fiber carriers (GFC) with an additionally deposited secondary layer of porous SiO2 for the process of carbon dioxide methanation. Ni-based GFCs were prepared using the surface thermosynthesis (STS) and pulse surface thermosynthesis (PSTS) methods, involves heat treatment of the catalyst with the supported Ni precursor at a high heating rate; such procedure was not applied earlier for production of CO2 methanation catalysts. The GFC sample prepared by the PSTS method with a fuel additive in the precursor composition is characterized by a more uniform distribution of Ni particles on the catalyst surface and better dispersion of Ni, smaller crystallite size: NiO crystallites in this freshly prepared GFCs are smaller than 10 nm and Ni crystallites in reduced catalysts are <30 nm. As a result, this sample demonstrated the highest apparent activity in the methanation reaction among all synthesized GFCs, it has also showed a significantly higher specific activity per unit mass of nickel compared to the commercial Ni-Al2O3 analogue. The synthesized catalysts are original, they can be effectively applied for development of novel highly efficient technologies for energy conversion/storage systems and greenhouse gas emission control.